INRW: INTELLIGENT IOT NON-REVENUE WATER MONITORING SYSTEM - DESIGN AND DEVELOPMENT OF DASHBOARD SYSTEM FOR THE EVALUATION OF WATER LOSS PROGRAM - SHUHAIMI, SHAMIRUL ASYRAF (IRC, 2019)
The purpose in this study is that a dashboard is: “a visual display of the most important information needed to achieve one or more objectives consolidated and arranged on a single screen, so the information can be monitored at a glance”. The main different objectives of using dashboards are the ability to ensure consistency, planning, communication and monitoring. In the era of Big data, the power of data to manage our decisions indicates that fact-based decision making is increasingly important within organizations. Therefore, specialists able to support decision making utilize descriptive, predictive, and prescriptive analytics are increasingly in demand to provide data analysis of the vast amount of information that is available. It is crucial for any organization to measure and improve its performance. The ability to numerically measure performance offers accurate data that facilitates analysis, helping to improve the quality of organizations. Use of IIoT and power BI dashboard is continuing to grow globally as a key method for addressing leakage and NRW. Specific data points valuable to detecting NRW such as pressure, flow, and tank level data are automatically pushed to operational analytics solutions by using these methods and provide a numerical foundation for analysis.